A benchmark of different starting modes of a passive Fuel Cell/Ultracapacitor hybrid source for an electric vehicle application. (March 2021) - Jacome, Andres; Dépature, Clément; Boulon, Loïc; Solano, Javier
Abstract: A benchmark of different starting modes of a passive Fuel Cell (FC)/Ultracapacitors (UCs) hybrid source is presented. Passive hybridization consist to directly connect the FC and the UC without power electronics. Compared with active sources, passive hybridization presents some advantages: lower volume and weight, ease of implementation, and lower cost. However, the power distribution among the sources is no longer controllable. Additionally, the FC–UC passive hybrid source's start-up could lead to high inrush currents and faster FC degradation. A FC–UC passive hybrid source start-up is evaluated by simulations and experimentally. Three starting modes for an automobile application are considered: progressive starting, short circuit, and using a resistive pre-charge device. Highlights: Three starting procedures for a Fuel cell and ultracapacitors passive hybrid source are presented. A sizing methodology for the hybrid source is proposed. Pre-charge resistive procedure reduces the high inrush currents during the system passive connection.